The complete illustrated book of yoga - Vivekananda, Swami (New York : Solar Books, 2015)
Step-by-step exercises, illustrated with 146 photographs, and basic principles of diet and philosophy, by a teacher of Hatha Yoga in India.
Includes index.
Keywords: Yoga